2022
DOI: 10.1177/2333794x221126079
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Pacific Islander Doctors and Medical Students to Childhood Hearing Loss and Hearing Services: Results of a Structured Questionnaire Survey in SAMOA

Abstract: The Pacific Islands have among the highest global rates of childhood hearing loss in the world. Given the scarcity of ENT Specialists and audiologists in the region, the role of the wider health professional community in addressing preventable childhood hearing loss is crucial. A 10-item 5-point Likert scale questionnaire was administered to medical officers and medical students in Samoa. The statements aimed to investigate knowledge and attitudes to childhood hearing loss and hearing services. Overall, 95.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Despite knowledge deficits, the participants in this study demonstrated predominantly positive attitudes towards childhood hearing loss. This finding resonates with prior studies by Moller et al [9], Yerraguntla et al [12], and Kaspar et al [23], highlighting the commitment exhibited by PCPs in the study to provide the best care and services to children with hearing loss.…”
Section: Plos Onesupporting
confidence: 90%
“…Despite knowledge deficits, the participants in this study demonstrated predominantly positive attitudes towards childhood hearing loss. This finding resonates with prior studies by Moller et al [9], Yerraguntla et al [12], and Kaspar et al [23], highlighting the commitment exhibited by PCPs in the study to provide the best care and services to children with hearing loss.…”
Section: Plos Onesupporting
confidence: 90%
“…The second study similarly investigated awareness and perceptions towards childhood hearing impairment among urban and rural/remote female caregivers in Samoa, and also found high support for hearing health services for infants (98%) and school students (97.3%) (Kaspar et al, 2023). A third study investigated awareness and perceptions towards childhood hearing impairment among doctors and medical students in Samoa (Kaspar et al, 2022), and again the results showed positive support for the implementation of childhood hearing services (95.8%). In order to investigate health professional readiness to meet caregiver support for community-based ear and hearing health healthcare, further assessment of current and future health professionals’ attitudes towards such services in the Pacific Islands is desirable.…”
Section: Review Of Literaturementioning
confidence: 98%
“…The ENT Clinic of Samoa will continue to partner with the National University of Samoa School of Nursing for ongoing curriculum development that prepares future nurses for supporting ear and hearing healthcare. Curriculum development on childhood hearing health may be extended beyond the School of Nursing, and considered for other courses such as Inclusive Education (i.e., role of teachers for students with hearing difficulties) and/or the Masters of Public Health (i.e., integration of school-based hearing screening into the national PEN Fa’a Samoa public health initiative) (Kaspar et al, 2023).…”
Section: Implications For Practicementioning
confidence: 99%